Building the Ecoliteracy Intelligent of Student Through the Citizen Project Model at FKIP UNIBBA - Febri Restu Widianto; Sari Sri Handani; Dena Mustika (International Journal of Ethno-Sciences and Education Research, 2024)
This research is motivated by the challenges faced by humans today related to the environment. Ecoliteracy intelligence needs to be developed especially for FKIP students at the University of Bale Bandung, who are prospective educators to create environmentally friendly character- based learning. This study aims to analyze: (1) the eco-literacy intelligence of FKIP Bale University Bandung students; (2) Factors that become obstacles and potential in building eco- literacy intelligence for FKIP UNIBBA students; and (3) The implementation of eco-literacy competencies through project citizens. The method used was a survey in four study programs, with respondents consisting of study program heads/secretaries, teaching staff, and students. The results of the study show that (1) In general, FKIP UNIBBA students have good eco- literacy intelligence in preserving the environment; (2) The potential effort to increase students' eco- literacy intelligence is implemented in an integrated curriculum in each study program, especially those related to ethics and environmental awareness courses, a global perspective, PLSBS Sundanese Culture which is a special subject based on local wisdom of FKIP UNIBBA. Meanwhile, the obstacles in efforts to increase the eco-literacy intelligence of FKIP UNIBBA students are the absence of a policy to provide a special budget for the provision of environmentally friendly facilities; (3) The project citizen model is a character-based learning model to create smart and wise citizens who are built through ecological intelligence. Strategic policies to create a green and environmentally friendly campus need to be improved.